Inexact Block LU Preconditioners for Incompressible Fluids with Flow Rate Conditions (Communications in Computational Physics, 2026)
When studying the dynamics of incompressible fluids in bounded domains, the only available data often provide average flow rate conditions on portions of the domain's boundary. In engineering applications a common practice to complete these conditions is to prescribe a Dirichlet condition by assuming a priori a spatial profile for the velocity field. However, this strongly influences the accuracy of the numerical solution. A more mathematically sound approach is to prescribe the flow rate conditions using Lagrange multipliers, resulting in an augmented weak formulation of the Navier-Stokes problem.In this paper we start from the SIMPLE preconditioner, introduced so far for the standard Navier-Stokes equations, and we derive two preconditioners for the monolithic solution of the augmented problem. This can be useful in complex applications where splitting the computation of the velocity/pressure and Lagrange multipliers numerical solutions can be very expensive. In particular, we investigate the numerical performance of the preconditioners in both idealized and real-life scenarios. Finally, we also highlight the advantages of treating flow rate conditions with a Lagrange multipliers approach instead of prescribing a Dirichlet condition.
Keywords: Flow rate conditions; Lagrange multipliers; SIMPLE preconditioner; incompressible Navier-Stokes equations; computational fluid-dynamics